In search of peace: Ahmadi women’s experiences in conflict transformation - Nina Mariani Noor; Siti Syamsiyatun; JB. Banawiratma (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2015)
In the last few years, religious conflicts involving a minority Muslim group, Ahmadiyya, have risendramatically in Indonesia; the most recent being the attack on the Ahmadiyya community in CikeusikBanten, West Java, where three Ahmadis were killed and the sealing of Al Mishbah Mosque by localgovernment of Bekasi West Java. Understanding the context of violent conflict and the ways individualAhmadi women take agency to challenge such oppression is an important first step in creating a moreequitable and peaceful Indonesia. To examine the experience of Ahmadi women exercising their agencyin conflict transformation, this qualitative research was conducted in four areas of Indonesia: Bogor,Kuningan, Yogyakarta and Lombok, by gathering data from the narratives of Ahmadi women whoactively participate in Lajnah Imaillah, an Ahmadiyya’s women’s organization. This research highlightsthree stages of conflict transformation that the women employed: 1) asking for government help; 2)taking physical action to defend their rights; and 3) defining themselves as Indonesian citizens who havethe same rights as others. Through these actions, they show their ability to help others, transformingthe conflict by forming better relationships and understanding with other Indonesian citizens.